A descriptive survey of lower-limb amputees admitted to Tygerberg Hospital (1985-1987) - Hendry, Jennifer Anne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Epidemiology))__University of Stellenbosch, 1993.